Sistem Rekomendasi Pemilihan Sekolah Menengah Atas Menggunakan Metode Naive Bayes - Salma, Triana Dewi, Yusuf Sulistyo Nugroho, S.T.,M.Eng (2016)
Every year the education in Indonesia grows along with the increasing number of schools or educational institutions. Meanwhile, based on the data from Department of Education in Sragen, the increasing number of schools also offset by the increasing number of students in each year. These schools are established close together in the region as well as the high school in Sragen. Today, many schools are not only compete in terms of academic achievement through school and the accreditation but also compete in the quality of a good education to attract prospective students. However, problems frequently encountered are many factors that ultimately lies behind the student to choose a candidate school, either external or internal factors of the school. Therefore that students are required to intelligently determine the best school with the criteria. This research was conducted in order to help students to choose candidates for the best high school in accordance with the desired criteria. The implementation of the Naïve Bayes method is used in this study to recommend the best school for students that utilize data from high schools in Sragen. Naïve Bayes method is applied to find the greatest probability of all instances of the target attributes such as distance, tuition fees, accreditation, graduation rates and the least average value of UAN. Result from this study is a recommendation system that can help to provide information on high schools that match the criteria. Thus, the best high school that appropriate to the proposed criteria can be recommended to the students as well.